Reflections and Insights on the Evolution of the Biological Remediation of Contaminated Soils - Alkorta, Itziar; Garbisu, Carlos (Frontiers in Environmental Science, 2021)
The field of soil biological remediation was initially focused on the use of microorganisms. For organic contaminants, biostimulation and bioaugmentation were the strategies of choice. For heavy metals, bioremediation was centered on the feasibility of using microorganisms to reduce metal toxicity. Partly due to the impossibility to degrade metals, phytoremediation emerged proposing the use of plants to extract them (phytoextraction) or reduce their bioavailability (phytostabilization). Later, microbial-assisted phytoremediation addressed the inoculation of plant growth-promoting microorganisms to improve phytoremediation efficiency. Similarly, plant-assisted bioremediation examined the stimulatory effect of plant growth on the microbial degradation of soil contaminants. The combination of plants and microorganisms is nowadays often recommended for mixed contaminated soils. Finally, phytomanagement emerged as a phytotechnology focused on the use of plants and associated microorganisms to decrease contaminant linkages, maximize ecosystem services, and provide economic revenues. Although biological remediation methods have been in use for decades, the truth is that they have not yet yielded the expected results. Here, we claim that much more research is needed to make the most of the many ways that microorganisms have evolutionary developed to access the contaminants and to better understand the soil microbial networks responsible, to a great extent, for soil functioning.